Magnetite particles enhance recovery of methanogenic efficiency in propionate and acetate-overloaded anaerobic digesters: Insights into microbial community dynamics - Kim, Minjae; Song, Minsu; Kang, Seonmin; Jung, Sungyun; Rhie, Mi Na; Rhee, Chaeyoung; Shin, Seung Gu; Lee, Joonyeob (Journal of environmental management, 2025)
The potential of magnetite particles to enhance anaerobic digestion has been reported, but their effectiveness in improving digester robustness under propionate and acetate overloads remains unclear in continuous operation. This study evaluated the effects of magnetite nanoparticles (50–100 nm) supplemented at 20 mM on the recovery of anaerobic digesters overloaded with propionate or acetate (5–8 g-COD/L) through long-term continuous anaerobic digestion experiments and examined microbial community dynamics associated with this recovery. Magnetite particles-supplemented digesters showed 124–226 % and 23–43 % higher methanogenic degradation rates for propionate and acetate overloads (2.5–2.8 and 1.6–2.0 g-COD/L/d, respectively) than the control digesters. This enhancement reduced recovery time by 51–66 % following propionate-shock-loads (p < 0.05, Student's t-test) and up to 23 % following acetate-shock-loads. Inhibition caused by 8 g-COD/L propionate-shock-loads was alleviated in the magnetite particles-supplemented digesters. Magnetite particles facilitated the preferential enrichment of distinct microbial communities, among which Syntrophobacter, Peptoclostridium, and Methanothrix showed increased relative abundances that positively correlated with the accelerated recovery of overloaded digesters (p < 0.05, Spearman correlation test). These shifts and the enrichment of predicted functional genes for propionate and acetate oxidation and stress response underscore the role of magnetite supplementation in reinforcing possible microbial community robustness and resilience. Collectively, these findings demonstrate that magnetite particle supplementation is an effective strategy to strengthen digester robustness against propionate- and acetate-shock-overloads, providing a practical basis for developing more resilient anaerobic digestion processes and mitigation strategies for VFA-overloaded systems. [Display omitted] •Magnetite particles enhanced digester robustness against propionate overloads.•Magnetite enhanced propionate and acetate degradation rates by up to 226 % and 43 %.•Magnetite addition alleviated propionate stress, shortening recovery time by 66 %.•Dominance of Methanothrix and syntrophs with magnetite improved degradation.•Magnetite facilitated microbial community resilience, promoting digester stability.